PENERAPAN PENGGUNAAN MEDIA POHON AKSARA DALAM MENINGKATKAN KEMAMPUAN MEMBACA PERMULAAN DI KELAS 1 SISWA SD NEGERI 1 NGINGIT - Octavia, Nurul; Chrisyarani, Denna Delawanti; Setiawan, Dwi Agus (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research was prompted by the low initial reading skills of first-grade students at SDN 1 Ngingit due to conventional teaching methods. The study aims to enhance these skills through the